Oral contraceptive pill use is associated with localized decreases in cortical thickness. Issue 7 (2nd April 2015) - Petersen, Nicole; Touroutoglou, Alexandra; Andreano, Joseph M.; Cahill, Larry
Abstract Oral contraceptive pills (OCs), which are used to prevent pregnancy by the majority of women in the United States, contain steroid hormones that may affect the brain's structure and function. In this investigation, we tested the hypothesis that OC use is associated with differences in brain structure using a hypothesis‐driven, surface‐based approach. In 90 women, (44 OC users, 46 naturally‐cycling women), we compared the cortical thickness of brain regions that participate in the salience network and the default mode network, as well as the volume of subcortical regions in these networks. We found that OC use was associated with significantly lower cortical thickness measurements in the lateral orbitofrontal cortex and the posterior cingulate cortex. These regions are believed to be important for responding to rewards and evaluating internal states/incoming stimuli, respectively. Further investigations are needed to determine if cortical thinning in these regions are associated with behavioral changes, and also to identify whether OC use is causally or only indirectly related to these changes in brain morphology. Hum Brain Mapp 36:2644–2654, 2015. © 2015 Wiley Periodicals, Inc.